Ramos, M. C. (2019). "Desierto de mar y otros poemas" , ilustrada por Asiain Lora, M. ,Madrid: Editorial SM, 104 pp. - S. Amorós, Àngels (Ondina - Ondine, 2022)
Reseña de Àngels S. Amorós, Ramos, M. C. (2019). Desierto de mar y otros poemas, ilustrada por Asiain Lora, M., Madrid: Editorial SM, 104 pp.